2015
DOI: 10.5455/ijmsph.2015.3110201477
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of overweight and obesity among elderly population in an urban area of Puducherry

Abstract: million people who are obese. [3] According to a report of the World Health Organization, 2.8 million adults die each year as a result of being overweight or obese. In addition, 44% of the diabetes, 23% of the ischemic heart disease, and 7-41% of certain cancers are attributable to overweight and obesity. [3] In the twenty-first century, obesity has reached epidemic proportions in India, with morbid obesity affecting 5% of the country's population. [4] India is following a trend of other developing countries t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 4 publications
(5 reference statements)
1
15
0
Order By: Relevance
“…Kappa statistic was calculated for different MUAC cutoff and respected BMI cutoffs. [17][18][19][20] [9,10,21] After a fully comprehensive literature search, we believed that the present study is the first to examine if MUAC can be a useful, alternative, and practical screening and predictive The present study revealed AUCs for MUAC for different BMI values ranged from 0.79 to 0.91. All these findings clearly state that MUAC can be a simpler alternative to BMI for screening the elderly for overweight or obesity.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Kappa statistic was calculated for different MUAC cutoff and respected BMI cutoffs. [17][18][19][20] [9,10,21] After a fully comprehensive literature search, we believed that the present study is the first to examine if MUAC can be a useful, alternative, and practical screening and predictive The present study revealed AUCs for MUAC for different BMI values ranged from 0.79 to 0.91. All these findings clearly state that MUAC can be a simpler alternative to BMI for screening the elderly for overweight or obesity.…”
Section: Methodsmentioning
confidence: 98%
“…Central obesity in elderly population of India is a major health problem which is supported by the studies done by Rajkamal et al in South India and by Swami et al in Chandigarh where they have found 41.4% and 33% obese elderly population. [9,10] Nutritional assessment in low-resource settings like rural areas in our country often relies on non-invasive, simple, and affordable anthropometric methods. Anthropometric methods have been used to describe nutritional status and rapidly identify at-risk groups for appropriate interventions.…”
Section: Introductionmentioning
confidence: 99%
“…7 Another study done in rural areas of Puducherry showed that 27.7% of the women participants had a BMI>25.…”
Section: Introductionmentioning
confidence: 98%
“…[3][4][5][6] A study done in urban area of Puducherry showed the prevalence of overweight was 41.4% and of obesity was 4.5%. 7 Another study done in rural areas of Puducherry showed that 27.7% of the women participants had a BMI>25. 8 This shows that there is an anticipated increased risk of obesity inflicted maternal adverse outcomes among women in Puducherry.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation